ANALISA PROTEKSI OVER CURRENT RELAY (OCR) DAN GROUND FAULT RELAY (GFR) PADA TRANSFORMATOR DAYA GARDU INDUK - Abdul Multi; Thufail Addaus (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2022)
ABSTRACT In the electric power distribution system, the power transformer is an equipment plays an important role in a substation. In a distribution system, a fault cannot be predicted. This fault can be in the form of a 3-phase, 2-phase, or 1-phase short-circuit fault to ground. In order to prevent this, a good and reliable protective equipment is needed, one of which is the Over Current Relay (OCR) and Ground Fault Relay (GFR) which are used as backup protection for power transformers. The work principle of the OCR is to detect the presence of a short-circuit current between phases and the work principle of the GFR is to detect a short-circuit current from the phase to ground, the results of the analysis carried out describe when the fault current exceeds the predetermined setting value then Over Current relay and Ground fault Relay takes instantaneous decisions or by slowing down the opening of the PMT in the event of a disturbance. After doing the calculations, for the setting current (OCR) on the 150 kV side, 277.2 A was obtained with the TMS (OCR) time setting of 0.31 and for the setting current (GFR) on the 150 kV side, 35.22 A was obtained with the TMS time setting ( GFR) is 0.44. For the setting current (OCR) on the 20 kV side, 2,078.4 A is obtained with the TMS time setting (OCR) of 0.23 and for the setting current (GFR) on the 20 kV side, 96.07 A is obtained with the TMS time setting (GFR) namely 0.3. Keywords: Transformer, Over Current Relay, Ground Fault Relay, OCR, GFR